Homogeneity, Returns to Scale and (Log)Concavity - Per Hjertstrand (Research Institute of Industrial Economics (IFN), 2020)
This brief note shows that if a production function, f, is quasiconcave, increasing and homogeneous, then f is concave if it displays nonincreasing returns to scale, and f is logconcave if it displays increasing returns to scale.
Keywords: D21; 330; Homogeneity; Returns to scale; Rho-concavity